Quality of life measurement in rosacea. Position statement of the European Academy of Dermatology and Venereology Task Forces on Quality of Life and Patient Oriented Outcomes and Acne, Rosacea and Hidradenitis Suppurativa. (6th February 2023) - Chernyshov, P. V.; Finlay, A. Y.; Tomas‐Aragones, L.; Steinhoff, M.; Manolache, L.; Pustisek, N.; Dessinioti, C.; Svensson, A.; Marron, S. E.; Bewley, A.; Salavastru, C.; Dréno, B.; et al.
Abstract: The European Academy of Dermatology and Venereology (EADV) Task Forces (TFs) on Quality of Life (QoL) and Patient‐Oriented Outcomes and Acne, Rosacea and Hidradenitis Suppurativa (ARHS) do not recommend the use of any generic instrument as a single method of Health Related (HR) QoL assessment in rosacea, except when comparing quimp (quality of life impairment) in rosacea patients with that in other non‐dermatologic skin diseases and/or healthy controls. The EADV TFs on QoL and Patient‐Oriented Outcomes and ARHS recommend the use of the dermatology‐specific HRQoL instrument the Dermatology Life Quality Index (DLQI) and the rosacea‐specific HRQoL instrument RosaQoL in rosacea patients. The DLQI minimal clinically important difference may be used as a marker of clinical efficacy of the treatment and DLQI score banding of 0 or 1 corresponding to no effect on patients' HRQoL could be an important treatment goal. This information may be added to consensuses and guidelines for rosacea.